2019
DOI: 10.1590/1678-4162-11006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the growth of major mastitis-causing pathogens by non-aureus Staphylococcus isolates using the cross-streaking method

Abstract: Inhibition of the growth of major mastitis-causing pathogens by non-aureus Staphylococcus isolates using the cross-streaking method [Comunicação: Inibição do crescimento dos principais patógenos causadores de mastite por isolados de estafilococos não aureus pelo método cross-streaking]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The authors observed pronounced inhibitory effects of S. chromogenes isolates against S. aureus, variable effects against S. dysgalactiae and S. uberis, and no effects against E. coli, suggesting that this susceptibility to NAS is more pronounced against phylogenetically-related bacterial species (i.e., Gram positive). Other studies also reported only a modest effect against Gram-negative bacteria; however, this effect was observed by using the semiquantitative growth inhibition assay [15,23,24,31]. On the other hand, bacterial growth can also be limited by the availability of nutrients, which differs according to the local environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed pronounced inhibitory effects of S. chromogenes isolates against S. aureus, variable effects against S. dysgalactiae and S. uberis, and no effects against E. coli, suggesting that this susceptibility to NAS is more pronounced against phylogenetically-related bacterial species (i.e., Gram positive). Other studies also reported only a modest effect against Gram-negative bacteria; however, this effect was observed by using the semiquantitative growth inhibition assay [15,23,24,31]. On the other hand, bacterial growth can also be limited by the availability of nutrients, which differs according to the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common finding that NAS isolated from TA are more likely to produce antagonist substances against other bacteria [15,29]. Moreover, protection against S. aureus by the S. simulans species has previously been suggested [18,30], although most of the studies have reported more pronounced inhibitory effects by S. chromogenes [15,23,24,29] and a modest effect by S. epidermidis isolates. The effect observed for the latter species is most probably because these species are usually transferred from human skin to cows during the milking process [37,38] and their virulence properties are limited [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of non-aureus staphylococci (NAS) such as S. chromogenes on the teat apex during prepartum has been associated with lower somatic cell counts shortly after calving, which is used as an indicator for subclinical mastitis (De Vliegher, 2003). S. chromogenes isolated from the teat apex has also been shown to partially or fully inhibit S. aureus in vitro (Ferronatto et al, 2019). The reason for this apparent inhibition is thought to be the production of antimicrobial peptides (AMPs) capable of targeting and attenuating growth of other microorganisms (Cotter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly considered to be minor mastitis pathogens causing only a slight increase of the milk somatic cell count (SCC) [ 10 12 ] with no impact on milk yield. Other studies have suggested a protective effect of bovine NAS against, among other bacteria, S. aureus [ 13 17 ], including the repression of agr related virulence factors of S. aureus [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%